Histopathology of Metarhizium anisopliae Entomopathogenic fungus Infected Larve of Musca domestica L. (Diptera : Muscidae) - Obaid, W. B.; Mehdi, N. S.; Mohammad, H.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study consist of using Metarhizium anisopliae as abioinsecticide against house fly Musca domestica L. For controlling it biologicaly its Larvae were treated by sprying them directly and sprying their food with 2.3 Ã— 10 8 conidia / ml of Metarhizium anisopliae . Infected Larve showed symptoms of slugishness and slow growth. Histopathological study of the dead Larve showed Conidial adhesion and germ tube penetrations through body wall and begining of fungus hyphal growth under the body wall and hyphal invasion in haemocoel and gut.